The impact of cisplatinum‐based chemotherapy on ventricular function and cardiovascular risk factors in female survivors after malignant germ cell cancer. (14th July 2015) - Murbraech, Klaus; Solheim, Olesya; Aulie, Hanne M.; Fossa, Sophie D.; Aakhus, Svend
Abstract: Aims: Among male cancer survivors, cisplatinum‐based chemotherapy (CBCT) is associated with impaired left ventricle (LV) diastolic function, increased risk of metabolic syndrome, and increased cardiovascular morbidity and mortality. Comparable data in females are limited. The long‐term effects of cisplatin on right ventricle (RV) function are unknown in both genders. We aimed to investigate the impact of CBCT on cardiovascular risk factors and cardiac function in female survivors after malignant ovarian germ cell tumour (MOGCT). Methods and results: This national cross‐sectional follow‐up study recruited MOGCT survivors, diagnosed from 1980–09 ( n = 153). Seventy‐four (48%) participated in out‐patient visit, of whom 41 had received CBCT (62% of all CBCT): median age, 35 years (range, 18–64 years); median time since CBCT, 14 years (range, 5–31 years). Participants were categorized into high‐CBCT ( n = 19) and low‐CBCT ( n = 22) groups and compared with age‐matched healthy females. All participants underwent laboratory tests and echocardiography to determine cardiac function. Compared with low‐CBCT participants, the high‐CBCT group showed significantly impaired RV function, as evaluated by tricuspid annular plane systolic excursion (22.6 ± 2.4 mm vs. 26.3 ± 3.6 mm; P < 0.001); RV S' (10.7 ± 1.9 cm/s vs. 12.4 ± 2.3 cm/s; P = 0.01); RV global longitudinal strain (−23.4 ± 2.4% vs. −25.7 ± 3.7%; P = 0.02), and tricuspid annular displacement (21 ± 2 mm vs. 24 ± 3 mm; P = 0.001). LV diastolic function was impaired in the high‐CBCT group compared with controls. Patients and controls exhibited similar metabolic syndrome prevalences. Conclusions: Among long‐term survivors of MOGCT, CBCT was associated with impaired RV function and LV diastolic function. Unlike men, women do not appear to have an elevated risk of metabolic syndrome after CBCT.